From License Raj to Unregulated Chaos (A Critical Analysis of the Shenanigans of the Government) - D. K. Balkrisnan, Dr. Gurudev Sahil, Surabhi Sharma (International Journal of Modern Agriculture, 2021)
The BJP regime has brought forth a flurry of three legislations which basically intends to do away with the existing structure. The legislations intend to gradually do away with the concept of APMC, mandi system and minimum support price. Driven with the dream of an â€œatmanirbharâ€ India the regime is trying to bring in legislations which plan to make the farmers self-dependent overnight. It is always better to remove the bottlenecks in an existing plan rather than scrapping the existing system completely and bringing a new system altogether. The new legislations are brought forth by the government because according to surveys the MSPs have been inefficient to ameliorate the issues of the farmers. So instead of ensuring effective procurement of crops and ensuring MSPs at variety of crops the government has very conveniently chosen to gradually do away with MSPs. The government via these changes wishes to bring end to the impediment of middlemen. The very logic or rationale behind this is if the middlemen are eliminated from the process then the farmers and also the consumers will be benefitted. However the legislations donâ€™t provide for enough safeguards which would discontinue the practice of middlemen. Rather if these legislations are analysed deeply it can be seen that the legislations sort of announce corporate bigwigs into the agrarian scenario and pull the plug on MSPs gradually. Also the change in essential commodities Act ensures that these corporate bigwigs will also get opportunity to artificially increase the prices as products like pulses, lentils, onion etc have been removed from the essential commodities Act. These therefore removes any sort of restriction on the corporate bigwigs to hoard these products and artificially create inflation.